Sasi and Its Relation to the Economic Development and Marine Preservation (Case Study: Raja Ampat) - Adiastuti, Anugerah; Hartanto, Heri; Utomowati, Rahning (UI Scholars Hub, 2019)
Raja Ampat, West Papua, Indonesia, is one among many marine tourism spots such as Derawan, Bunaken, Wakatobi and Tiga Gili. Raja Ampat is known for its diversity, rich coral reefs and marine resources. Raja Ampat’s characteristic is not only based on their beauty of marine natural resources but also its tradition, culture and living indigenous law. The existing indigenous law in Raja Ampat is called “SASI”. This tradition and living law has an important relation in sustaining tourism activities and the variety of marine activities that can be carried out in the ocean, particularly in marine protected areas on Raja Ampat. This writing is meant to analyze Sasi; to examine Sasi and its relation to economic development; and to analyze the impact of Sasi’s implementation on marine preservation for marine sustainability. It appears that Sasi’s implementation as the indigenous living law on Raja Ampat offers positive advantages including restoration and livelihood of the marine environment (incorporating with their marine natural resources). Therefore, the existence of Sasi on Raja Ampat is able to maintain the economic progress and marine environment sustainability.